Dynamic characteristics of QWIP-HBT-LED optoelectronic integrated devices - Eladl, Sh.M.; Nasr, A.; Aboshosha, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
This paper presents an evaluation of the transient performance of an optoelectronic integrated device. This device is composed of a quantum well infrared photodetector (QWIP), a heterojunction bipolar transistor (HBT) and a light emitting diode (LED). It is called as QWIP-HBT-LED optoelectronic integrated device. Evaluation of its transient response is based on the frequency response of the constituent devices. Analytical expressions describing the transient behavior, output derivative as a measure of speed, and the rise time are derived. The numerical results show that the transient performance of the version under consideration is mainly based on the individual quantum efficiencies and is improved with their growth. The device speed and rise time are enhanced with the increase of the cut-off frequency of HBT.